An analysis of the main approaches to the process of law formation in the context of historical types of the understanding of law: terminological aspect - Roybis, Ivan (Journal of the Belarusian State University. Law, 2019)
The article deals with the dynamics of change in the main approaches to the process of law-formation depending on the particular type of law understanding, existing in a certain period of time, in the context of searching for the most appropriate term. Two main categories that describe the formation of law – «law-formation» and «law-making» are distinguished. It is concluded that, according to the analysis of the main approaches of law understanding the process of law-formation was not considered fully by the legal doctrine. It is concluded that there is a lack of knowledge on the interrelationships between various paradigms of law understanding with the process of the formation of law on both practical and theoretical levels. The assumption is made about the formation of the integrative type of law understanding that will allow to rethink and change the approach to the understanding of law and to move from legal monism to the acceptance of the possibility that various factors might impact law-formation.
Keywords: law-formation; law-making; law understanding; types of law understanding